The Patenting Behavior of Academic Founders - Sascha G. Walter; Arne Schmidt; Achim Walter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2010)
This study explores why academic entrepreneurs patent their inventions before and after creating a firm. Drawing on start-up data combined with patent data, we specifically examine the impact of five, relatively under-researched factors (scientific field, pace of technological development, technological uncertainty, entrepreneurial orientation, and patent effectiveness. The study shows that some scientific fields, technological uncertainty, and patent effectiveness are positively related to patent propensity, both before and after founding. The effects of pace of technological development and entrepreneurial orientation were timespecific. Our study suggests that patenting by academic entrepreneurs is driven by special rationales and that prior research on full-time scientists and established firms does not necessarily generalize to them. We discuss the implications of our findings both in terms of contribution to the current literature and technology transfer policies.
Keywords: 650; academic patenting